Estimation of the Rural Dog Population Within a Mega-City: An Example in Jiading District, Shanghai - Wu, Xiujuan; Yu, Viola Yifei; Huang, Zhong; Lu, Jun; Tang, Wenhong; Shen, Sufang; Xia, Luming; Zhu, Jiuchao; Wang, Jian; Chen, Jiansheng; Chen, Guanming; Bian, Yi; et al. (Frontiers in Veterinary Science, 2021)
Rural dog populations have long been recognized to be inadequately managed in terms of disease control and prevention. In this study we consider dog management in rural Shanghai and its implications for rabies control in the entire metropolitan area of Shanghai. The prerequisite to improve rabies vaccination coverage in rural Shanghai depends on a proper enumeration of the total rural dog population in Shanghai. In this study we selected one of the nine administrative districts in Shanghai (Jiading), within which there are 7 towns and 2 industrial zones (township-level division) that contain agricultural areas. A total of 9 villages (rabies model villages) were chosen from each township-level division in Jiading, and an additional 3 non-model villages were also included in the study. A household questionnaire survey was implemented in all 12 villages recruited. In 3 of the model villages and the 3 non-model villages chosen as a comparison, two methods of enumeration – a sight-resight survey and a household questionnaire survey – were implemented. Results from the household survey in these 6 villages showed that among the total 1560 owned dogs, 80.4% were Chinese Garden Dogs, 69.1% were aged 1 to 3 years, 49.2% were homebred, and 88.3% were kept for the purpose of guarding the house. However, only 3.7% of the owned dogs were desexed. There was a higher proportion of chained or confined dogs in model compared to non-model villages. The model villages had a much higher rabies vaccination coverage (100%) and a much smaller number of stray dogs. It was also identified that the two enumeration methods yielded similar counts（P=0.12）, particularly within smaller villages. From the questionnaire survey implemented within all 12 villages and based on the average human-to-dog ratio, the total rural dog population of Jiading district was estimated to be 24,058. This study generated information on the general demographics of the rural dog population in Jiading, and demonstrates an approach to the study of rural dog populations within the context of a megacity. In such a context, rural dog populations need to be considered as a critical component of animal and public health.